Grandmother's Nursery Rhymes - Las Nanas de Abuelita - Nelly Palacio Jaramillo (U.S.A Henry Holt and Co. (BYR, 1996)
This lovingly gathered bilingual Spanish/ English collection includes traditional favorite nursery rhymes, lullabies, and tongue-twisting verse from South America.